Lymphocyte Activation Dynamics Is Shaped by Hereditary Components at Chromosome Region 17q12-q21. - Amado Carreras-Sureda (PLoS ONE, 2016)
Single nucleotide polymorphisms (SNPs) located in the chromosome region 17q12-q21 are risk factors for asthma. Particularly, there are cis-regulatory haplotypes within this region that regulate differentially the expression levels of ORMDL3, GSDMB and ZPBP2 genes. Remarkably, ORMDL3 has been shown to modulate lymphocyte activation parameters in a heterologous expression system. In this context, it has been shown that Th2 and Th17 cytokine production is affected by SNPs in this region. Therefore, we aim to assess the impact of hereditary components within region 17q12-q21 on the activation profile of human T lymphocytes, focusing on the haplotype formed by allelic variants of SNPs rs7216389 and rs12936231. We measured calcium influx and activation markers, as well as the proliferation rate upon T cell activation. Haplotype-dependent differences in mRNA expression levels of IL-2 and INF-γ were observed at early times after activation. In addition, the allelic variants of these SNPs impacted on the extent of calcium influx in resting lymphocytes and altered proliferation rates in a dose dependent manner. As a result, the asthma risk haplotype carriers showed a lower threshold of saturation during activation. Finally, we confirmed differences in activation marker expression by flow cytometry using phytohemagglutinin, a strong polyclonal stimulus. Altogether, our data suggest that the genetic component of pro-inflammatory pathologies present in this chromosome region could be explained by different T lymphocyte activation dynamics depending on individual allelic heredity.